2020
DOI: 10.1029/2020gl088989
|View full text |Cite
|
Sign up to set email alerts
|

Eocene Rotation of the Northeastern Central Tibetan Plateau Indicating Stepwise Compressions and Eastward Extrusions

Abstract: When and how the TP underwent uplift and deformation are still under heated debate. We present paleomagnetic evidence for the NB in the northeastern central TP to help decipher the potential plateau deformation mechanism. Magnetostratigraphy with zircon U‐Pb age of volcanic rock demonstrates that the NB basin deposited during 52.5–35.0 Ma. Paleomagnetic declinations indicate that the basin experienced counterclockwise rotation of 25.9 ± 7.2° during 52–46 Ma and clockwise rotation of 24.4 ± 9.7° during 41–35 Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 133 publications
(315 reference statements)
2
27
0
Order By: Relevance
“…In addition, the local different rotational deformation within the terrane was generally associated with the transition of major tectonic lines composed of faults and fold axes (Tong et al., 2013). It should be noted that the Nangqian Basin and the Gonjo Basin on the north side of the EHS experienced counterclockwise rotation and clockwise rotation during ∼52‐46 Ma, respectively (S. H. Li et al., 2020; Tong et al., 2017; Zhang et al., 2020). The opposite rotational characteristics of the two basins indicate that the eastern part of the Qiangtang Terrane possibly experienced continuous local different rotational deformation since the Eocene, related to the dual function of compression between the main body of the Indian Plate and Eurasia and the northward indentation of the Indian Plate and West Burma Block into the Eastern Himalayan orogenic belt.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the local different rotational deformation within the terrane was generally associated with the transition of major tectonic lines composed of faults and fold axes (Tong et al., 2013). It should be noted that the Nangqian Basin and the Gonjo Basin on the north side of the EHS experienced counterclockwise rotation and clockwise rotation during ∼52‐46 Ma, respectively (S. H. Li et al., 2020; Tong et al., 2017; Zhang et al., 2020). The opposite rotational characteristics of the two basins indicate that the eastern part of the Qiangtang Terrane possibly experienced continuous local different rotational deformation since the Eocene, related to the dual function of compression between the main body of the Indian Plate and Eurasia and the northward indentation of the Indian Plate and West Burma Block into the Eastern Himalayan orogenic belt.…”
Section: Discussionmentioning
confidence: 99%
“…In the northern region near latitudes of ∼35°, where though present-day left-lateral slip on east-west planes and therefore counterclockwise rotation characterizes current deformation (Duvall and Clark, 2010), total amounts of clockwise rotation are ∼15°-25° (Dupont-Nivet et al, 2004Fang et al, 2003;Liu et al, 2010;Wang et al, 2011;Yan et al, 2006). Near the latitude of the syntaxis, most estimates of clockwise rotation are 25°-50° (e.g., Kornfeld et al, 2014;Otofuji et al, 1990;Todrani et al, 2020;Zhang et al, 2020). Farther south in Yunnan, yet larger amounts of clockwise rotation exceeding 50° (Chen et al, 1995;Huang and Opdyke, 1993;Li et al, 2018;Tong et al, 2016) and reaching 90° (Sato et al, 2001) have been reported, but many sites show smaller amounts of rotation.…”
Section: Comparison Of Palaeomagnetic Declination Anomalies With Gps Observed Rotationsmentioning
confidence: 99%
“…However, during the period from ∼47.6 to 40 Ma, the occurrence of a relatively low sedimentation rate with no significant provenance change in the Linxia Basin suggests a stable tectonic setting on the Tibetan Plateau (Feng et al., 2022). This time period with a stable tectonic setting on the Tibetan Plateau also coincided with no rotation between 48 and 41 Ma in the Xining and Gonjo Basins (Dupont‐Nivet et al., 2008; S. Li et al., 2020) and with nonsignificant rotation during ∼46–41 Ma in the Nangqian Basin (W. Zhang, Fang, et al., 2020). Therefore, the shift from an active to a stable tectonic setting at ∼47 Ma coincided with the transition from relatively wet to dry climate on the NE Tibetan Plateau, implying that the impact of Tibetan Plateau uplift on this regional climate change was minor during this time period.…”
Section: Discussionmentioning
confidence: 83%
“…As discussed above in Section 5.2, the high magnetic intensity during ∼51.7–47.6 Ma in the Linxia Basin was related to the change in provenance caused by the accelerated growth of the West Qinling under relatively wet climatic conditions. The provenance shift, together with the multistage increases in the sedimentation rate in the DHJ section, was approximately synchronous with the orogenesis as a result of the India–Asia collision (e.g., Molnar & Stock, 2009; Rowley, 1996) and the origin of the basins on the NE Tibetan Plateau (Dai et al., 2006; Fang, Fang, et al., 2019; Fang, Galy, et al., 2019; Feng et al., 2022; Ji et al., 2017; W. Wang et al., 2016; Yue et al., 2001) and northeastern central Tibetan Plateau (W. Zhang, Fang, et al., 2020). In addition, thermochronological evidence also suggests that the West Qinling Mts (Clark et al., 2010; P. He et al., 2017; Y. Zhang, Wang, et al., 2020), Qilian Mts (P. He et al., 2018, 2021; Jian et al., 2018), and Kunlun Mts (G. C. Wang, Xiang, et al., 2007) underwent synchronous fast exhumation and accelerated growth in the early Eocene.…”
Section: Discussionmentioning
confidence: 99%